2023
DOI: 10.1039/d2ra07095b
|View full text |Cite
|
Sign up to set email alerts
|

A review on adsorption characteristics and influencing mechanism of heavy metals in farmland soil

Abstract: The accumulation of heavy metals in soil and crops is considered to be a severe environmental problem due to its various harmful effects on animals and plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…18 Various chemical mechanisms are involved in the adsorption process, including ion exchange, cationbridging, ion-dipole interactions, ligand exchange, charge transfer, hydrogen bonding, and van der Waals forces. Furthermore, current study by Yu et al 19 has shown that a number of variables, including pH, temperature, and the presence of other environmental pollutants, affect the sorption of pesticides. Phosphoric, phosphonic, or phosphoramidic acid can form ester or thiol derivatives that are mostly organophosphorus compounds.…”
Section: Introductionmentioning
confidence: 92%
“…18 Various chemical mechanisms are involved in the adsorption process, including ion exchange, cationbridging, ion-dipole interactions, ligand exchange, charge transfer, hydrogen bonding, and van der Waals forces. Furthermore, current study by Yu et al 19 has shown that a number of variables, including pH, temperature, and the presence of other environmental pollutants, affect the sorption of pesticides. Phosphoric, phosphonic, or phosphoramidic acid can form ester or thiol derivatives that are mostly organophosphorus compounds.…”
Section: Introductionmentioning
confidence: 92%
“…7,20,21 The utilization of raw materials from nature as well as their modified varieties and hybrids for the elimination of metals has been recognized as the most efficient method of purification, considering some essential factors such as availability, affordability, scalability, and environmental concerns. 22,23 Bentonite and related derivatives have received a great deal of attention as exceptionally efficient adsorbents. 24,25 Bentonite is a frequently employed geological term that refers to a kind of sedimentary rock that primarily consists of smectite clay minerals, specifically montmorillonite, along with other varieties of clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have advised the employment of both synthetic and natural adsorbents for adsorption-mediated elimination of soluble metal ions such as Cd­(II). This approach is regarded as a simple, reliable, and cost-effective elimination method. ,, Nevertheless, the investigation of appropriate adsorbents remains a compelling area of study, implementing crucial criteria for selection including material accessibility, manufacturing expenses, recycling potential, adsorption capacity, equilibrium behavior, and kinetic rates. ,, The utilization of raw materials from nature as well as their modified varieties and hybrids for the elimination of metals has been recognized as the most efficient method of purification, considering some essential factors such as availability, affordability, scalability, and environmental concerns. , …”
Section: Introductionmentioning
confidence: 99%
“…8 Nanozymes have diverse advantages, including low usage and high efficiency in crop enhancement. Thus, nanozymes have been used to alleviate plant abiotic stress in various ways, 9 such as reducing stress caused by salinity, 10 temperature fluctuations, 11,12 drought, 13 waterlogging, 14 soil heavy metal pollution, 15 etc. For instance, Chen et al found that nano Fe 2 O 3 could increase the photosynthesis and biomass of peanuts.…”
Section: Introductionmentioning
confidence: 99%